Financial Performance Comparative Analysis of Sub-Industry Companies in Oil and Gas Drilling Services - Fitra Syafaat (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study conducts a comparative analysis of the financial performance of PT Elnusa Tbk and PT Apexindo Pratama Duta Tbk, two prominent Indonesian oil and gas drilling service companies, from 2019 to 2023. Against the backdrop of fluctuating oil prices and evolving industry regulations, the research addresses the critical need to evaluate liquidity, profitability, and leverage dynamics to assess operational resilience and strategic decision-making efficacy. Utilizing a quantitative approach, financial ratios—Current Ratio, Debt-to-Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM)—were calculated using audited financial statements to compare managerial efficiency and capital structure stability. Results revealed distinct trajectories: PT Elnusa demonstrated moderate liquidity (Current Ratio: 1.45–1.74) with gradual post-pandemic recovery in profitability (NPM: 2.88% to 5.98% by 2023), while PT Apexindo exhibited superior short-term liquidity (Current Ratio peaking at 8.28 in 2020) but severe profitability challenges, including negative ROA (-0.52) and ROE (-97.50%) in 2022. Both companies faced leverage pressures, though PT Elnusa maintained a marginally stable DER (0.74–0.93) compared to PT Apexindo’s volatile debt reliance (DER fluctuations from 6.24 to 0.99). The findings underscore PT Elnusa’s relative operational stability and PT Apexindo’s liquidity-strength-profitability trade-offs, offering stakeholders critical insights into risk management and investment prioritization within Indonesia’s energy services sector.